Crime, Inequality and Subsidized Housing: Evidence from South Africa - Roxana Manea; Patrizio Piraino; Martina Viarengo (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We study the relationship between housing inequality and crime in South Africa. We create a novel panel dataset combining information on crimes at the police station level with census data. We find that housing inequality explains a significant share of the variation in both property and violent crimes, net of spillover effects, time and district fixed effects. An increase of one standard deviation in housing inequality explains between 9 and 13 percent of crime increases. Additionally, we show that a prominent post-apartheid housing program for low-income South Africans led to a reduction in inequality and a decline in violent crimes. Together, these findings suggest the important role that equality in housing conditions can play in the reduction of crime in an emerging economy context.
Keywords: D63; O10; K14; 330; inequality; crime; economic development